Numerical study of demountable shear wall system for multistory precast concrete buildings. (December 2021) - Naserpour, Afshin; Fathi, Mojtaba
Abstract: The aim of this paper is to propose a demountable shear wall (DSW) system for multistory precast concrete buildings. For this purpose, instead of a large wall panel, several slender walls are used by connecting to adjacent beams. To evaluate the efficiency of the DSW system, nonlinear cyclic and time history analyses are performed on eighteen 4-, 8- and 12-story models, including three conventional shear wall models and fifteen DSW models with various wall numbers. The results indicate that for DSW system, when using more walls with a smaller width, the structural deformation tends from flexural-type to almost shear-type. This result prevents the plastic strain from concentrating on the columns and walls of the first story and causes the damage to be uniformly distributed on the walls of all stories. The DSW models exhibit hysteretic behavior without significant strength degradation at high drift levels. Also, DSW models with more walls, while increasing the ductility factor (up to 30%) and creating a more uniform distribution of drifts, reveal less value of maximum floor acceleration (up to 48%) and story shear (up to 53%), compared to conventional shear wall models.